2010
DOI: 10.1111/j.1365-2672.2009.04651.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory activity of potential probiotic yeast strains in the dorsal air pouch system and the gut mucosa

Abstract: Aims:  To determine the immunostimulatory activity of 15 presumptive probiotic yeast strains in the dorsal air pouch system in comparison with their activity in the gut mucosa. Methods and Results:  Presumptive probiotic yeast strains previously isolated from human gastrointestinal tract and Feta cheese were further characterized genotypically and biochemically. The Saccharomyces cerevisiae 982, Saccharomyces boulardii KK1 and Kluyveromyces lactis 630 strains exhibited in the air pouch increased polymorphonucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
0
18
0
4
Order By: Relevance
“…Strains of S. boulardii, S. cerevisiae, and Saccharomyces unisporus have also been isolated from alcoholic beverages such as Brazilian cachaça (Martins et al 2005), Ghanaian sorghum beer (Van der Aa Kühle et al 2005) and Northern Caucasus kefir (Diosma et al 2014), from Greek feta cheese (Kourelis et al 2010), Italian sourdough bread (Perricone et al 2014), and from children's feces (Kourelis et al 2010). All these strains have demonstrated probiotic potential, as indicated by optimal growth temperature at 37°C, resistance to GIT stresses, and other properties.…”
Section: Introductionmentioning
confidence: 98%
“…Strains of S. boulardii, S. cerevisiae, and Saccharomyces unisporus have also been isolated from alcoholic beverages such as Brazilian cachaça (Martins et al 2005), Ghanaian sorghum beer (Van der Aa Kühle et al 2005) and Northern Caucasus kefir (Diosma et al 2014), from Greek feta cheese (Kourelis et al 2010), Italian sourdough bread (Perricone et al 2014), and from children's feces (Kourelis et al 2010). All these strains have demonstrated probiotic potential, as indicated by optimal growth temperature at 37°C, resistance to GIT stresses, and other properties.…”
Section: Introductionmentioning
confidence: 98%
“…Yeast fungi are known to be symbiotic with mammals. Saccharomyces yeasts may occur naturally in humans where they limit inflammatory response and increase immune health; these have also been used as probiotics ( Kourelis et al, 2010). Filamentous fungi, many of which decompose complex carbohydrates such as cellulose and lignin, have been studied in the digestive tracts of insects ( Lichtwardt, 2008) and the rumen of cattle ( Theodorou et al, 2005), and have been reported in human fecal samples ( Finegold et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces Boulardii KK1 Strain, a Presumptive Probiotic, Improves Gluten-Induced Enteropathy Because probiotics have been shown to hydrolyse gliadin in vitro, 16 we examined whether presumptive probiotics with established immunoregulatory activity 14,15 have an effect in vivo in the gluten-induced mouse model for CD. The hydrolytic activity of L. paracasei DC412, DC205 or S. boulardii KK1 strains was first verified in vitro by preparing wheat flour fermentation in the presence of these strains.…”
Section: Gluten Induces Adaptive and Innate Immunity Mediators In Thementioning
confidence: 99%
“…All lactobacilli were stored at À801C in MRS broth with 25% glycerol, and KK1 cultures were maintained at 41C in a YEGP agar slope. 14,15 Yeast or lactobacilli were harvested at 18-24 h of culturing and resuspended at the appropriate concentration (CFU/ml) according to the McFarland standard.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%